Detecting SQL Injection Using Correlative Log Analysis - Sreeja, T; Manna Sheela Rani Chetty, Dr; Babu Boddu, Sekhar (International Journal of Engineering and Technology, 2018)
The spiking landscape of cyber-attacks is reflecting its trend towards invoking vulnerabilities in a web application. The vulnerabilities seem to be over-growing second by second beside being over-coming time to time. The reason behind is, new attack vectors are often being deployed by the threat actors. The global cyber security market alone has brought a turnover of about 350 billion, which shows how wide the attack landscape is and how expensive it is to detect, protect and respond to the cyber issues. Most of the security experts have quoted that, the average cost of a data breach will exceed to 150million by 2020 and about 80 percent of the global demography were nowhere aware of such attacks. From the past few years, SQL injection is acting as a major vector in breaching the sensitive data. Detecting SQL injection through log correlation is the most effective methodology utilized under adaptive environments seeking no tool investigation. This paper exposes a detection methodology of an SQL injection attack without any mere concentration on automated tools. The paper goes with a motto of detection through configuring the available resources like web server,database,and an IDS in a way of creating adaptable environment that can bring the entire attacker information through log analysis. The paper would represent the attacker phases in a finite automata.Â Â